Climate migration and social transformation: The case of West Africa - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Although migration has long been an adaptive strategy in West Africa driven by multiple interrelated factors, climate migration is expected to increase as the impacts of climate change worsen. Climate migration is widely expected to accelerate existing trends, including the movement of people from the dry Sahelian belt to coastal countries and urbanization.